Influence of rootstocks on white root rot (Dematophora necatrix) resistance in apple (Malus baccata) - KUMAR, ANIL; ATTRI, BRIJ LAL; KISHOR, ARUN; DEBNATH, SOVAN; MER, MUKESH SINGH; NARAYAN, RAJ (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted under polyhouse and field conditions during 2013, 2014 and 2015 to evaluate the level of resistance of less known apple rootstock, i.e. Paron (Malus baccata var. himalaica) and some popular rootstocks of the region (MM 106, MM 111, M 9 and Srinagar crab) against white root rot disease. All the test rootstocks were grafted with CITH Lodh Apple-1 before their use in field conditions. Paron showed high resistance against D. necatrix by exhibiting least mortality (15.33%) at highest test dose (10 g/kg soil) of inoculum in pot culture under polyhouse, whereas other test rootstocks showed 100 percent mortality at this dose of inoculum. In the field, Paron showed no wilting symptoms on scion cultivar even after 60 days of inoculation, it showed least bronzing and inward cupping of leaves (3.25%), defoliation (3.50%), necrosis on bark (21 mm), wood (17 mm) and vascular tissues (23 mm). It was rated as resistant against D. necatrix as compared to other test rootstocks on the basis of significantly lowest disease severity (4.35%) and least effect of test pathogen inoculation on its above and below ground parts. Srinagar crab was rated as highly susceptible in comparison as, it exhibited significantly highest disease severity (69.80%). From this study, it can be inferred that the rootstock of Paron should be used for shaping production of apple in Kumaon region of Uttarakhand.